Use of Film and PowerPoint Media for Awareness of Sexual Violence in Adolescents Through Group Guidance - Kusumawardani, Anggraeni; Hinggardipta, Ratnasari; Herdi, Herdi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
The rapid growth and change in the world has encouraged the use of technology in various fields, including education and learning. Guidance and counseling in schools as part of the education system in Indonesia, uses technology to improve the quality of its services to students. This study aims to measure the effectiveness of using PowerPoint films and media in increasing students' awareness about sexual harassment through group guidance. Action research methods with one group pre-test and post-test and descriptive analysis were used to support the analysis of the results in this study. A total of fifteen students participated in this study. The results showed that the use of films and PowerPoint was effectively applied in group counseling services to increase students' awareness of sexual harassment.